Development of indicators to assess quality and patient pathways in interdisciplinary care for patients with 14 ambulatory-care-sensitive conditions in Germany - Wiebke Schüttig; Ronja Flemming; Christiane Höhling Mosler; Verena Leve; Olaf Reddemann; Annemarie Schultz; Emmanuelle Brua; Matthias Brittner; Frank Meyer; Johannes Pollmanns; Johnannes Martin; Thomas Czihal; et al. (BMC, 2022)
Abstract Background In settings like the ambulatory care sector in Germany, where data on the outcomes of interdisciplinary health services provided by multiple office-based physicians are not always readily available, our study aims to develop a set of indicators of health care quality and utilization for 14 groups of ambulatory-care-sensitive conditions based on routine data. These may improve the provision of health care by informing discussions in quality circles and other meetings of networks of physicians who share the same patients. Methods Our set of indicators was developed as part of the larger Accountable Care in Deutschland (ACD) project using a pragmatic consensus approach. The six stages of the approach drew upon a review of the literature; the expertise of physicians, health services researchers, and representatives of physician associations and statutory health insurers; and the results of a pilot study with six informal network meetings of office-based physicians who share the same patients. Results The process resulted in a set of 248 general and disease specific indicators for 14 disease groups. The set provides information on the quality of care provided and on patient pathways, covering patient characteristics, physician visits, ambulatory care processes, pharmaceutical prescriptions and outcome indicators. The disease groups with the most indicators were ischemic heart diseases, diabetes and heart failure. Conclusion Our set of indicators provides useful information on patients' health care use, health care processes and health outcomes for 14 commonly treated groups of ambulatory-care-sensitive conditions. This information can inform discussions in interdisciplinary quality circles in the ambulatory sector and foster patient-centered care.